2021
DOI: 10.1002/ptr.7135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grapes/grape products on glycemic response: A systematic review and meta‐analysis of randomized controlled trials

Abstract: The aim of this study was to perform a systematic review and meta‐analysis of randomized clinical trials (RCTs) to examine the effect of grapes/grape products supplementation on glycemic indices in adults. Our systematic search to find relevant RCTs was performed up to February 2020 using PubMed, Scopus, ISI Web of Science, Cochrane Library, and Google Scholar. Based on the heterogeneity between included studies, a random effects or a fixed model was applied in the meta‐analysis, and results were expressed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…56 Several therapeutic strategies such as natural extracts have been developed with the objective of improving the glycemic response. 57 There has been interest in MLE in the scientific community, and ML and MLE are used for hypoglycemia, obesity, and T2DM 39 because they are rich in phenolics, flavonoids, and polysaccharides, especially 1-DNJ, which is a unique active ingredient in ML. 58,59…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Several therapeutic strategies such as natural extracts have been developed with the objective of improving the glycemic response. 57 There has been interest in MLE in the scientific community, and ML and MLE are used for hypoglycemia, obesity, and T2DM 39 because they are rich in phenolics, flavonoids, and polysaccharides, especially 1-DNJ, which is a unique active ingredient in ML. 58,59…”
Section: Discussionmentioning
confidence: 99%
“…objective of improving the glycemic response. 57 There has been interest in MLE in the scientific community, and ML and MLE are used for hypoglycemia, obesity, and T2DM 39 because they are rich in phenolics, flavonoids, and polysaccharides, especially 1-DNJ, which is a unique active ingredient in ML. 58,59 To the best of our knowledge, this is the first meta-analysis to examine the effects of ML/MLE on glycemic traits.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…For instance, the consumption of grape powder, grape skin extract and grape seed oil successfully prevented increased fasting blood glucose and dyslipidemia in mice, and red grape pomace extract, which comes from winemaking by-products, was able to suppress postprandial hyperglycemia (PPHG). 8 These grape products are also capable of decreasing oxidative stress and inflammation and promoting cardiac health. 9 Blueberry, a "superfruit" that is commonly consumed in Western countries and has gained increasing popularity in Asia in recent years, is well-linked to several health-promoting effects.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that certain foods and nutrients have good effects on the liver (Abbasnezhad et al, 2019; Asbaghi, Ghanbari, et al, 2020; Asbaghi, Kashkooli, et al, 2021; Asbaghi, Naeini, et al, 2021; Mousavi et al, 2021; Yousefi Rad et al, 2019). Grapes, a group of fruits with high polyphenol content, have been shown to exert several antioxidants, antiinflammatory, and anti‐diabetic properties (Asbaghi, Nazarian, et al, 2020; Ghalishourani et al, 2021; Moodi et al, 2021; Ramchandani, Chettiyar, & Pakhale, 2010), and are widely consumed around the world. The results of a meta‐analysis study including randomized controlled trials (RCTs) by Asbaghi, Nazarian, et al (2020) showed that administration of grape seed extract (GSE) significantly lowered C‐reactive protein (CRP) levels as a marker of acute phase inflammation produced by the liver.…”
Section: Introductionmentioning
confidence: 99%